Optimizing Egg Production in Indonesia Using a Robust Stochastic Approach of Planning - Sri Sulandjari (Journal of Management and Entrepreneurship Research, 2024)
Objective: This study aims to address the challenges of demand variability in Indonesia's poultry industry, which often leads to production inefficiencies, including overproduction and shortages, by proposing a stochastic production plan that minimizes costs associated with these inefficiencies within the context of the Indonesian cooperative funding system. Research Design & Methods: A stochastic lot-sizing model was developed, and an experiment was set up with five assessment strategies: basic average demand plan, high reliability demand coverage, cumulative demand, cyclical surplus adjustment, and consecutive surplus adjustment plans. The evaluation phase was conducted at two confidence levels (α = 0.90 and α = 0.95) to assess each plan's ability to minimize total costs effectively. Findings: The results revealed that the cumulative demand strategy consistently outperformed other strategies, minimizing surplus and shortage costs at both α = 0.90 and α = 0.95. This plan demonstrated the lowest surplus-to-demand ratio, making it the most effective in managing production inefficiencies and reducing costs. Implications and Recommendations: Implementing the cumulative demand strategy could significantly enhance the efficiency of production planning in Indonesia's poultry industry by reducing waste and optimizing resources, especially in cooperative funding systems. Contribution & Value Added: This study contributes to the literature by providing an empirical analysis of production planning strategies in the context of demand variability, offering valuable insights into cost-effective solutions for handling production inefficiencies in the poultry industry.